The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00004728-200001000-00006
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Lymphoma of Bronchus-Associated Lymphoid Tissue (BALT): CT Features in 10 Patients

Abstract: BALT lymphomas usually appear as airspace consolidation or nodules with air bronchogram or adjacent ground-glass attenuation at CT. These findings are similar to previous descriptions of pseudolymphomas. Multiple bilateral lesions are common in BALT lymphoma. Bubble-like radiolucencies have not been described previously and can be an additional finding of BALT lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 23 publications
2
39
0
6
Order By: Relevance
“…Bubble-like lucencies, ground-glass opacities and bronchial dilatation have also been described on CT [19].…”
Section: Imaging Findingsmentioning
confidence: 95%
“…Bubble-like lucencies, ground-glass opacities and bronchial dilatation have also been described on CT [19].…”
Section: Imaging Findingsmentioning
confidence: 95%
“…Computed tomography (CT) (figs. 1b and c), which is more sensitive than standard radiography, has demonstrated that the lesions are usually bilateral (60-70%) and multiple (70-77%) [25,26]. Nearly all these lesions contain clear areas corresponding to an intact bronchial lumen ( fig.…”
Section: Mucosa-associated Lymphoid Tissue Lymphomamentioning
confidence: 96%
“…[11,13,14]. Bae and coworkers classified the findings of chest CT in BALToma into four patterns, namely solitary nodule with consolidation, multiple nodular lesion with consolidation, bronchiolitis with bronchiectasis, and diffuse interstitial pneumonia [15]. It is difficult to arrive at a diagnosis of MALToma from an infiltrated lesion with manifest bronchiectasis of one entire lobe like the right lower lobe in the present case by recalling conventional chest imaging patterns of MALToma.…”
Section: Discussionmentioning
confidence: 88%